Perlindungan Korban dan Saksi Di Pengadilan Pidana Internasional Dalam Upaya Penegahan HAM - Natamihardja, Rudi (FIAT JUSTISIA)
The establishment of International criminal courts (ICC) is an attempt of enforcement of human rights to judge international criminal cases: the crime of genocide, crimes against humanity, war crimes and the crime of aggression. Its creation is a universal respect of human rights and a state law. This research tried to answer how ICC protects the victims and witness and how they can get their reparations. This research used a normative research that analyze of Rome Statute and Rules of Procedure and Evidence of ICC and Resolution of assemble general on the creation of International Criminal Tribunal for Former Yugoslavia (ICTY) and International Criminal Court for Ruanda (ICTR). I found that ICC gave more protection to the victims and witness than ICTY and ICTR. The victim had also the rights for reparation, material and immaterial.